Alcohol-Induced Portal Hypertension Presenting With Massive Ascites-A Case Report - .G.V, Karunya shree; Balasubramaniam, Aishwarya; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sri, M.K.Sundar (Journal of Neonatal Surgery, 2025)
Background: Portal hypertension and ascites are serious complications of chronic liver disease. In alcohol-related cirrhosis, recurrent ascites despite optimal therapy may suggest rare vascular entities such as porto-sinusoidal vascular disease (PSVD), which can mimic cirrhosis but follow a different clinical course. Case Presentation: A 47-year-old male with a 30-year history of chronic alcohol use and comorbid diabetes and hypertension presented with abdominal distension, pedal oedema, dyspnoea, and oliguria. He had two prior admissions for similar complaints. Examination revealed icterus, ascites, anasarca, and mild splenomegaly. Laboratory tests showed anaemia, thrombocytopenia, and elevated transaminases. Ultrasound suggested chronic liver disease with ascites. The patient was treated with intravenous furosemide, oral spironolactone, propranolol, antibiotics, and underwent large-volume paracentesis. Supportive measures included a salt-restricted, high-protein diet. Clinical improvement was noted during hospitalization. He was diagnosed with decompensated liver disease with portal hypertension, most likely due to alcoholic cirrhosis. However, recurrent ascites despite therapy raised the possibility of an overlapping vascular liver disorder such as PSVD. Conclusion: This case highlights the need to consider alternative diagnoses, such as PSVD, in patients with alcohol-induced liver disease who experience frequent decompensations. Multidisciplinary management, alcohol cessation counselling, and long-term monitoring are crucial. Advanced diagnostics like HVPG measurement or liver biopsy may help differentiate atypical presentations and guide therapy.